Vibration Simulation of the cylindrical reservoir shell containing fluid vortex with the help of Vib-Shape software - Moradi, Hossein; Barati, Farzan (Ciência e Natura, 2015)
This paper addresses the simulation of the vibrational behavior of a flat-bottomed cylindrical reservoir in different levels of fluid vortex with the help of Vib-Shape software. The reservoir is equipped with a mixer, which creates fluid vortex and required loading. The compliance of the shell vibration mode shape of the mentioned model obtained from the collected data and simulation in the aforementioned software is compared with the mode shapes derived from the Donnell‘s theory. The results are in the good agreement with the governing theories of the problem.